Estudio de las técnicas de replicación de bases de datos y su incidencia en el alto desempeño, caso aplicativo replicación de la base de datos Oracle bajo plataforma gnu-linux de la empresa tevcol. - Padilla Narváez, Walter Ramiro (2013)
The TEVCOL company was established in 1967 is dedicated to serving the guardianship, transportation of securities and custodian of jewelry is in the service of Ecuador in the course of 45 years, this company is located in twenty two cities across the country distributed in different branches both the coast, mountains, east and the Galapagos Islands is characterized by a solid company offering its services to the public.